Christianity under Islam in Jerusalem : the question of the holy sites in early Ottoman times - Peri, ʻOded (Ottoman Empire and its heritage, 2001)
Based on official Ottoman records found in the registers of the kadi's court in Jerusalem as well as the Prime Ministry's Archives in Istanbul, this study offers a thorough treatment of Ottoman policy with respect to the Holy Sites during the first two centuries of Ottoman rule in Jerusalem.